Modified congklak game in the teaching of the English second conditional: an experimental study - Sundari Purwaningsih; Wida Mulyanti (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2019)
The notion to nurture local culture through English Language Teaching sparks an idea to incorporate an Indonesian traditional game, congklak, into a grammar class. Oftentimes, practicing grammar in a mechanical and monotonous way makes students struggle more than they already have with attempting to grasp grammar concepts. Consequently, only those with strong internal motivation, which are often small in number, are eager to engage in the practice. This study was intended to investigate the effectiveness of congklak game in helping adult learners acquire the English second conditional. One intact class of learners in an EFL university setting (final pool: n = 20) was randomly assigned to two groups (congklak game and non-congklak game). A pretest and an immediate posttest were administered to measure the participant’s mastery of the target grammatical forms. Results from the posttest revealed that the congklak game group significantly outperformed the non-congklak game group. The findings lend support to the possibility of adapting and modifying Indonesian traditional games as effective pedagogical means to facilitate EFL learners in acquiring grammatical forms in a much more interesting way.